2021
DOI: 10.1093/hmg/ddab211
|View full text |Cite
|
Sign up to set email alerts
|

In-frame deletion of SPECC1L microtubule association domain results in gain-of-function phenotypes affecting embryonic tissue movement and fusion events

Abstract: Patients with autosomal dominant SPECC1L variants show syndromic malformations, including hypertelorism, cleft palate and omphalocele. These SPECC1L variants largely cluster in the second coiled-coil domain (CCD2), which facilitates association with microtubules. To study SPECC1L function in mice, we first generated a null allele (Specc1lΔEx4) lacking the entire SPECC1L protein. Homozygous mutants for these truncations died perinatally without cleft palate or omphalocele. Given the clustering of human variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…We found that almost 39% of C57BL/6J female embryos had not completed PS elevation by E14.25, whereas 100% of C57BL/6J male embryos showed completed PS elevation. We also recently reported a mouse model ( Specc1l ΔCCD2 ) on a mostly C57BL/6J background (N3 generation) mixed with some FVB/NJ that the cleft palate phenotype in heterozygotes was more prevalent in female (17%) vs. male (5%) embryos (Goering et al 2021b). In fact, we saw a drastic decrease in Specc1l ΔCCD2/+ heterozygous females as we further backcrossed to C57BL/6J background, with almost no Specc1l CCD2/+ females at weaning in the N7 generation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We found that almost 39% of C57BL/6J female embryos had not completed PS elevation by E14.25, whereas 100% of C57BL/6J male embryos showed completed PS elevation. We also recently reported a mouse model ( Specc1l ΔCCD2 ) on a mostly C57BL/6J background (N3 generation) mixed with some FVB/NJ that the cleft palate phenotype in heterozygotes was more prevalent in female (17%) vs. male (5%) embryos (Goering et al 2021b). In fact, we saw a drastic decrease in Specc1l ΔCCD2/+ heterozygous females as we further backcrossed to C57BL/6J background, with almost no Specc1l CCD2/+ females at weaning in the N7 generation.…”
Section: Discussionmentioning
confidence: 94%
“…We recently reported that deficiency of Specc1l resulted in PS elevation delay, but the PS shelves still eventually elevated and fused (Goering et al 2021b;Hall et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mice homozygous for a truncation allele showed an altered palatal rugae phenotype with oral adhesions and a reduction in interferon regulatory factor 6 (IRF6) in these structures, but no cleft palate [ 127 ]. Homozygotes for in-frame deletions in the second coiled-coil domain resulted in exencephaly, cleft palate, and ventral body wall closure defects [ 128 ], demonstrating the essential functional role of the coiled-coil domain. In vitro, functional studies demonstrated that SPECC1L colocalized with microtubules and filamentous actin in palatal mesenchymal cells [ 126 ].…”
Section: Contribution Of Cellular Adhesion To Craniofacial Morphogenesismentioning
confidence: 99%
“…Deletions or mutations in the coiled-coil domain severely affected its ability to associate with microtubules, reducing its ability to traffic in the cells and resulting in a perinuclear accumulation. This uneven distribution of SPECC1L in the cells resulted in increased actin and non-muscle myosin II bundles at the cell periphery [ 128 ]. Ultimately, the disrupted actomyosin cytoskeleton would affect cell alignment and coordinated movement required for elevation and fusion of the palatal shelves.…”
Section: Contribution Of Cellular Adhesion To Craniofacial Morphogenesismentioning
confidence: 99%